2019
DOI: 10.3390/nano9050675
|View full text |Cite
|
Sign up to set email alerts
|

High Catalytic Performance of Mn-Doped Ce-Zr Catalysts for Chlorobenzene Elimination

Abstract: Mn-Ce-Zr-O catalysts doped with varying Mn content were prepared and assessed for the catalytic combustion of chlorobenzene (CB). Nanosized MCZ-0.67 catalyst with amorphous phase exhibited a high and stable catalytic activity among the studied catalysts, achieving 90% CB conversion at 226 °C and withstanding stability tests, including time-based stability and the successive influence of various operating conditions. Meanwhile, the MCZ-0.67 catalyst used showed good recyclability by calcination in air. Characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In addition, the concentrations of Mn 4+ and O α species of oxidizing catalyst were crucial for the oxidative degradation of VOCs [43,49]. The order of the O β /O α follows in descending order as Mn 4+ /Mn 3+ , which was depicted as TP-Mn2Zr3 > MP-Mn2Zr3 > CP-Mn2Zr3, indicating the concentration of Mn 4+ was positively correlated with the content of oxygen vacancy [40].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the concentrations of Mn 4+ and O α species of oxidizing catalyst were crucial for the oxidative degradation of VOCs [43,49]. The order of the O β /O α follows in descending order as Mn 4+ /Mn 3+ , which was depicted as TP-Mn2Zr3 > MP-Mn2Zr3 > CP-Mn2Zr3, indicating the concentration of Mn 4+ was positively correlated with the content of oxygen vacancy [40].…”
Section: Discussionmentioning
confidence: 95%
“…It was worth noting that the XPS signal peak of Zr in TP-Mn2Zr3 and CP-Mn2Zr3 samples originated from the Mn-Zr solid solution, while the signal peak of Zr in the MP-Mn2Zr3 sample was derived from pure zirconia. This indicates that the Zr 4+ ion is very stable [43], though the Mn n+ ions were entered the framework of ZrO 2 . Moreover, the proportion of Mn, Zr, and O in the catalyst is related to the preparation routes (Table 3).…”
Section: Xps Analysismentioning
confidence: 96%
“…All of the samples exhibited type IV isotherms with a hysteresis loop in the relative pressure range P/P 0 = 0.9-1.0, which indicated that the mesoporous structure was excited in these samples. 20 Besides, all the samples showed a H2 type hysteresis loop. It could be seen that the SSA (specific surface area) was changed with the doped Sr amount.…”
Section: Textual and Structural Analysismentioning
confidence: 93%
“…5B), the peak located near 529 eV was attributed to the surface lattice oxygen (O 2À , denoted as O g ); the XPS peak of O 1s located near 531 eV is due to the surface active oxygen species (O 2 À , O 2 2À and O À , denoted as O b ), and the peak located above 533 eV is due to the hydroxyl species and chemically adsorbed water (denoted as O a ). 20,[42][43][44] Based on these fitting peak areas, it is obvious that Sr doping will significantly affect the distribution of oxygen species on the catalyst surface, especially for surface active oxygen. More specifically, after Sr doping, the O b /(O g + O b ) percentage on the surface of the perovskite catalysts significantly increased from 0.32 for the LC sample to 0.45 for the L 0.82 S 0.18 C sample.…”
Section: Chemical Statementioning
confidence: 99%
“…Although the former type is preferable in activity, the limited natural resources and low poisoning resistance hinder their wide application . In view of this, non-noble metal catalysts, especially Ce-based composite oxide catalysts, have aroused tremendous interest of researchers in recent years. CeO 2 , with good oxygen storage capacity and easy redox couple, has been proved to be a competent enhancer of the catalytic activity and textural properties of active oxides, such as MnO x , CuO, Cr 2 O 3 , CoO x , and V 2 O 5 . Such composite oxides present excellent catalytic performance in removing various pollutants, including Hg 0 , NO, CO, and volatile organic compounds (VOCs) …”
Section: Introductionmentioning
confidence: 99%